"Literature owes Africa a lot more than it has delivered": Chuma Nwokolo in conversation with Adaobi Nkeokelonye on literature and development. - Nkeokelonye, Adaobi (Journal of the African Literature Association, 2019)
In 2018, Nigerian Writer Chuma Nwokolo released his latest Novel, The Extinction of Menai, published by Ohio University Press. This tops the list of 10 other works – comprising of poetry and novels – since his debut work, The Extortionist, published by Macmillan Publishers in 1983. Nearing his fourth decade as a writer, Chuma Nwokolo's works are known to address social injustice with tales that are so particular about Africa and yet universal. Some of his other novels include Diaries of a Dead African (2003), The Ghost of Sani Abacha (2012), and One More Tale for the Road (2003). Dangerous Inheritance (1988) was also published by Macmillan Publishers as part of their Pacesetter series. His poetry collections are Memories of Stone (2006) and The Final Testament of a Minor God (2014). His latest novel focuses thematically on language and cultural extinction, showing the inseparable connections between them. Interestingly, the United Nations proclaimed year 2019 as "The International Year of Indigenous Languages". In February 2019, I conducted an interview with Chuma Nwokolo in his country home in Asaba, Nigeria. In the interview, Nwokolo discusses his position as a writer, and the relevance of the novel and its value as an authoritative source of knowledge on matters of social and political development. The themes of cultural resistance, extinction and remediation, dominant in Chuma Nwokolo's highly acclaimed works, The Extinction of Menai and Diaries of a Dead African, are discussed to offer insight to readers.